Технологічне забезпечення якості механічного оброблення опорних поверхоньшарошок тришарошкових бурових доліт - Яким, Ігор (КІНПАТРІ ЛТД, 2013)
Qualitative indices and efficiency of technology of rock bits cones bearing elements turning into the final size are analyzed.
Technological guarantee of quality of three-cone rock bits bearing surfaces mechanical treatment